AKUNTANSI PENGAKUAN PENDAPATAN DAN BIAYA KONTRAK JASA KONSTRUKSI (PSAK NO.34) PADA CV.XYZ - Putri B41111006, Mellyardila Ayuningtyas (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This research was implemented on CV.XYZ, which is a private company that engaged in construction service. This study is to determine "The accounting recognition of revenues and cost of construction contracts (PSAK No. 34) on CV.XYZ." This study was designed as a qualitative descriptive study. The data collection techniques is done by observation, interview, literature study and documentation.Data analysis was implemented by determining the construction contracts that will be analyzed to then apply PSAK No. 34 about construction contracts.The result showed that the company recognizes revenue based on the physical progress without calculating the costs that occur at this time. it is different with PSAK No.34 about construction contracts on paragraph 25 which states that the contract revenue is connected with the contract costs incurred in reaching the stage of completion, so that the revenues, expenses, and profit attributable reported by the completion of work proportionally.the results of this study also showed that there are differences in the recognition of retention fund, which company can get it after the work contract expires. Key Words : PSAK No.34, Revenue Recognition, Cost Recognition, Percentage of Completion